1993
DOI: 10.1093/oxfordjournals.humrep.a138260
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinology: The ovarian hyperstimulation syndrome in in-vitro fertilization: a Belgian multicentric study. I. Clinical and biological features

Abstract: The multicentric study regroups 128 cases of the ovarian hyperstimulation syndrome (OHSS) in in-vitro fertilization (IVF) and 256 selected controls. Values of serum oestradiol obtained from different laboratories were found to be normally distributed after logarithmic transformation. Comparative study of clinical and biological characteristics indicates that among OHSS patients (i) mean age was lower; (ii) tubal indications for IVF were less frequent; (iii) polycystic ovary-like conditions (i.e. hyperandrogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
104
1
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 0 publications
4
104
1
4
Order By: Relevance
“…Data regarding the frequency of VTE, however, comprise predominantly of case reports, case series, and relatively small cohort studies (Table S6). [116][117][118][119][120][121] In two large retrospective series of patients undergoing in vitro fertilization, thrombosis complicated 0.1% (95% CI, 0%-0.3%) 116 and 0.3% (95% CI, 0%-0.8%) 117 of cycles. A hospital-based case-control study demonstrated a fourfold increase in antenatal VTE with assisted reproductive technology for singleton pregnancies and a sixfold incidence in twin pregnancies but no statistically signifi cant association with postpartum VTE.…”
Section: Vte In Patients Using Assistedmentioning
confidence: 99%
“…Data regarding the frequency of VTE, however, comprise predominantly of case reports, case series, and relatively small cohort studies (Table S6). [116][117][118][119][120][121] In two large retrospective series of patients undergoing in vitro fertilization, thrombosis complicated 0.1% (95% CI, 0%-0.3%) 116 and 0.3% (95% CI, 0%-0.8%) 117 of cycles. A hospital-based case-control study demonstrated a fourfold increase in antenatal VTE with assisted reproductive technology for singleton pregnancies and a sixfold incidence in twin pregnancies but no statistically signifi cant association with postpartum VTE.…”
Section: Vte In Patients Using Assistedmentioning
confidence: 99%
“…Sex hormones are the major difference between female and male, and the effect of estrogen on coagulation is sometimes discussed, but controversy still remains. High estrogen level is associated with increased risk of ovarian hyperstimulation syndrome (OHSS, [8,9]) which may cause thrombosis [10][11][12], while estrogen has an antithrombotic effect on hormone replacement therapy (HRT) which may prevent coronary artery disease [13][14][15][16] and stroke [17,18]. Moreover, oral contraceptives are known to increase the risk of thrombosis [19][20][21][22][23][24][25].…”
mentioning
confidence: 99%
“…4,17,18 PCOS patients undergoing IVF have a high risk of developing ovarian hyperstimulation syndrome (OHSS), a serious iatrogenic complication of ovarian stimulation triggered by exogenous and/or endogenous hCG. 19 The introduction of GnRH antagonists in recent years with an established decrease in the incidence of OHSS as compared with GnRH agonists in the general population, might offer a new safer treatment option for these patients. 20,21 Gonadotrophin-releasing hormone (GnRH) antagonist is being increasingly used in COS for IVF from late 1990s.…”
Section: Introductionmentioning
confidence: 99%